Kandungan Serat Dan Zat Besi Biskuit Tepung Beras Merah (Oryza Nivara) Dan Tepung Daun Kelor (Moringa Oleifera): Kandungan Serat dan Zat Besi Biskuit Tepung Beras Merah (Oryza Nivara) dan Tepung Daun Kelor (Moringa Oleifera) - Cantika Zaddana; Dina Amalia; Zaldy Rusli; Cyntia Wahyuningrum (Universitas Airlangga, 2022)
Background: Brown rice and moringa leaf have superiority in Fiber dan Iron content, but most people rarely consume it because it tastes bitter and has unfavorable aroma. Making biscuits from brown rice flour and moringa leaf flour aims to utilize brown rice and moringa leaf to invent an innovation of functional food that can be accepted by the community. The main point of this study was to make biscuits that meet the quality requirements and contain high fiber and iron as well. Objectives: This study aimed to determine brown rice and moringa leaf flour biscuit that meet the quality requirements of SNI 2018, determined fiber and iron content in brown rice and moringa leaf flour biscuit, and determined the most preferred formula of biscuits by panelists. Methods: Biscuits were made into 5 different formulas with different concentrations of brown rice flour and moringa leaf flour, formula 1 (0% : 50%), formula 2 (50% : 0%), formula 3 (20% : 30%), formula 4 (25% : 25%) and formula 5 (30% : 20%). Biscuit quality test parameters include (water content test, ash content test, microbial contamination test, fat content test, protein content test, carbohydrate content test, fiber content analysis, iron content analysis and hedonic test). Results: Biscuits from brown rice and moringa leaf flour meet the quality requirements, while the results of the fiber content test of formula 1 have the highest fiber and iron content which are 23.295% and 211.41 mg/kg. Hedonic test showed that formula 5 was the best formula according to the panelists. Conclusions: All the biscuits formulas have met the quality requirements of SNI 2018. Biscuits formula with the highest content of fiber and iron came from Formula 1 yet Formula 5 was the most preferred formula by the panelists.